PREPARAÇÃO E CARACTERIZAÇÃO DE COMPÓSITOS CARVÃO ATIVADO/ARGILA PARA APLICAÇÃO EM ESTUDOS DE ADSORÇÃO DE CORANTES - Chagas, Neucineia Vieira (2013)
Increasing concern with the preservation of the environment, especially regarding water pollution due to the shortage of drinkable water worldwide, has led to an increase in studies which develop materials capable of removing color and metallic ions amongst other contaminants that make industrial effluent water improper to reuse and discharge. Activated charcoal has been used in water treatment stations; however, its high cost is still a disadvantage. This work aimed at evaluating the potential of composites obtained through the clay/activated charcoal combination in percentages of clays (Argel T and Voclay) equal to 15, 50 and 85% (m/m), calcined at 500°C, 700°C, 900°C to remove color from industrial effluents. Composites containing 50% clay, named AV50 and AC50 were characterized to evaluate their composition and structural and thermal properties, through X-ray diffraction analysis, X-ray energy dispersive spectroscopy (EDS), differential thermal analysis (DTA), thermogravimetry (TGA), infrared spectroscopic analysis, scanning electronic microscopy (SEM) and specific area (BET). The results of this characterization indicated intercalation of charcoal between the lamellas of the clay under study. Composites were tested for methylene blue dye adsorption and the materials that presented higher adsorption capacity were composites prepared at 500ºC. Factorial design 23 was used to evaluate the influence of parameters such as temperature, salt addition (KCl) and pH in the methylene blue dye adsorption with the composites AV50 and AC50 and the reactive dyes with the composite AC50. Results of the methylene blue dye adsorption as well as the reactive dyes revealed that the efficiency to remove dyes by the composite AC50 was around 97% and 70% respectively, revealing an important adsorbent for industrial application.